Application of targeted molecular and material property optimization to bacterial attachment-resistant (meth)acrylate polymers - Adlington, Kevin; Nguyen, Nam T.; Eaves, Elizabeth; Yang, Jing; Chang, Chien-Yi; Li, Jianing; Gower, Alexandra L.; Stimpson, Amy; Anderson, Daniel G.; Langer, Robert; Davies, Martyn C.; Hook, Andrew L.; et al. (American Chemical Society, 2016)
Developing medical devices that resist bacterial attachment and subsequent biofilm formation is highly desirable. In this paper, we report the optimization of the molecular structure and thus material properties of a range of (meth)acrylate copolymers which contain monomers reported to deliver bacterial resistance to surfaces. This optimization allows such monomers to be employed within novel coatings to reduce bacterial attachment to silicone urinary catheters. We show that the flexibility of copolymers can be tuned to match that of the silicone catheter substrate, by copolymerizing these polymers with a lower Tg monomer such that it passes the flexing fatigue tests as coatings upon catheters, that the homopolymers failed. Furthermore, the Tg values of the copolymers are shown to be readily estimated by the Fox equation. The bacterial resistance performance of these copolymers were typically found to be better than the neat silicone or a commercial silver containing hydrogel surface, when the monomer feed contained only 25 v% of the “hit” monomer. The method of initiation (either photo or thermal) was shown not to affect the bacterial resistance of the copolymers. Optimized synthesis conditions to ensure that the correct copolymer composition and to prevent the onset of gelation are detailed.